Baricitinib for systemic lupus erythematosus: a double-blind, randomised, placebo-controlled, phase 3 trial (SLE-BRAVE-II). Issue 10381 (25th March 2023) - Petri, Michelle; Bruce, Ian N; Dörner, Thomas; Tanaka, Yoshiya; Morand, Eric F; Kalunian, Kenneth C; Cardiel, Mario H; Silk, Maria E; Dickson, Christina L; Meszaros, Gabriella; Zhang, Lu; Jia, Bochao; et al.
Summary: Background: Baricitinib is an oral selective inhibitor of Janus kinase 1 and 2 approved for the treatment of rheumatoid arthritis, atopic dermatitis, and alopecia areata. In a 24-week phase 2 study in patients with systemic lupus erythematosus (SLE), baricitinib 4 mg significantly improved SLE disease activity compared with placebo. In this Article, we report the evaluation of efficacy and safety of baricitinib in patients with SLE in a 52-week phase 3 study. Methods: In this phase 3 double-blind, randomised, placebo-controlled study, SLE-BRAVE-II, patients (aged ≥18 years) with active SLE receiving stable background therapy were randomly assigned 1:1:1 to baricitinib 4 mg, baricitinib 2 mg, or placebo once daily for 52 weeks. The primary endpoint was the proportion of patients with an SLE Responder Index (SRI)-4 response at week 52 in the baricitinib 4 mg treatment group compared with placebo. Glucocorticoid tapering was encouraged but not required per protocol. The primary endpoint was assessed by logistic regression analysis with baseline disease activity, baseline corticosteroid dose, region, and treatment group in the model. Efficacy analyses were done on an intention-to-treat population, comprising all participants who were randomly assigned and received at least one dose of investigational product and who did not discontinue from the study for the reason of lost to follow-up at the first post-baseline visit. Safety analyses were done on all randomly assigned participants who received at least one dose of investigational product and who did not discontinue. This study is registered with ClinicalTrials.gov, NCT03616964, and is complete. Findings: A total of 775 patients were randomly assigned and received at least one dose of baricitinib 4 mg (n=258), baricitinib 2 mg (n=261), or placebo (n=256). There was no difference in the primary efficacy outcome of the proportion of SRI-4 responders at week 52 between participants who received baricitinib 4mg (121 [47%]; odds ratio 1·07 [95% CI 0·75 to 1·53]; difference with placebo 1·5 [95% CI –7·1 to 10·2]), 2 mg (120 [46%]; 1·05 [0·73 to 1·50]; 0·8 [–7·9 to 9·4]) and placebo (116 [46%]). None of the major secondary endpoints, including glucocorticoid tapering and time to first severe flare, were met. Serious adverse events were observed in 29 (11%) participants in the baricitinib 4 mg group, 35 (13%) in the baricitinib 2 mg group, and 22 (9%) in the placebo group. The safety profile of baricitinib in patients with SLE was consistent with the known baricitinib safety profile. Interpretation: Although phase 2 data suggested baricitinib as a potential treatment for patients with SLE, which was supported in SLE-BRAVE-I, this result was not replicated in SLE-BRAVE-II. No new safety signals were observed. Funding: Eli Lilly and Company.